Clinical, hematological, and immunological aspects of chronic myeloid leukemia: from molecular mechanisms to functional recovery - Kucher, Olena (ScienceRise: Medical Science, 2025)
The aim. To systematize and critically analyze data on clinical, hematological, molecular, and immunological determinants of chronic myeloid leukemia (CML) progression and treatment-free remission (TFR) with an emphasis on the pathophysiological mechanisms of leukemic stem cells (LSCs, CD26+), additional mutations (ASXL1, RUNX1, TP53), extracellular vesicles (EVs), ferroptosis, and immune control axes (PD-1/PD-L1, NKG2A-HLA-E), as well as the immunomodulatory effects of tyrosine kinase inhibitors (TKIs). Materials and methods. A targeted narrative review of guidelines (ELN, NCCN) and peer-reviewed publications from 2000–2025 from PubMed/PMC and specialized journals was conducted. Clinical predictors of response, pathophysiological mechanisms of resistance, and immune biomarkers of TFR success were summarized; a conceptual synthesis of evidence on the impact of different generations of TKIs on the immune landscape was performed, taking into account the post-COVID context. Results. CD26+ LSCs determine the early dynamics of the molecular response to ITC, but their persistence during TFR is not a sufficient predictor of relapse, emphasizing the leading role of immune surveillance. Additional ASXL1/RUNX1/TP53 mutations are associated with worse event-free survival and the need for early intensification of the strategy. EVs carry oncogenic signals (in particular, BCR-ABL1 transcript) and form an immunosuppressive microenvironment. Imatinib-resistant cell models show increased sensitivity to ferroptosis inducers, opening up a new therapeutic vector. Successful TFR is associated with higher numbers and maturity of NK cells (CD56+ CD16+ CD57+), the presence of memory-like NK (NKG2C+), high perforin content in NK and innate CD8+ T cells, and simultaneously low PD-1 expression. The NKG2A-HLA-E axis acts as an additional “brake” on cytotoxicity; its blockade potentially synergizes with anti-PD-1. Dasatinib, unlike imatinib/nilotinib, partially relieves inhibition via NKG2A, enhancing NK cytotoxicity. The COVID-19 pandemic has changed patients’ immune “fingerprints” (fewer NK cells with higher activation), which should be taken into account when selecting for TFR. Conclusions. Control of CML is a balance between deep cytoreduction with ITC and competent immune surveillance. Personalized tactics should combine: early identification of high-risk mutations, targeting CD26+ LSC, modification of EV signalling and induction of ferroptosis, as well as immunotherapeutic combinations (PD-1/PD-L1 and/or NKG2A-HLA-E blockade), which can increase the proportion of patients eligible for sustained TFR and bring the concept of functional recovery closer